Ecosustainable polymer nanomaterials for food packaging : innovative solutions, characterization needs, safety and environmental issues - Silvestre, Clara; Cimmino, Sossio (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2013)
'The book aims at looking at the complete life cycle of the packaging based on polymer nanomaterials by the contribution of several experts with the final aim to consider the balance between cost and performance, and risk and benefit and the health and environmental issues and the assessment of risk benefit and to contribute to identify the barriers that prevent a complete successful development of the new technology and the strategies to proceed further'--
Includes bibliographical references and index.
Keywords: Food -- Packaging -- Materials; Polymers; Nanostructured materials